Cerambycidae (Insecta: Coleoptera) of Quixadá, Ceará State, Brazil: new records and new species - Nascimento, Francisco E. De L.; Bravo, Freddy; Monnè, Miguel A. (Zootaxa, 2016)
A checklist of longhorn beetles (Coleoptera, Cerambycidae) of Quixadá County, Ceará State, Brazil is presented. Fifty-six specimens were examined and 32 species were identified, distributed in 29 genera, 19 tribes and two subfamilies. Fifteen species are new distributional records for Ceará State. Nealcidion latipenne (Bates, 1863) is recorded by the first time in Caatinga Biome. Lathroeus immaculatus sp. nov. (Acanthocinini, Lamiinae) is described and figured.